2005
DOI: 10.1088/0967-3334/26/4/012
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of cardiac waves on fetal magnetocardiographic signals

Abstract: Fetal magnetocardiography (fMCG) provides fetal cardiac traces useful for the prenatal monitoring of fetal heart function. In this paper, we describe an analytical model (ACWD) for the automatic detection of cardiac waves boundaries that works on fetal signals reconstructed from fMCG by means of independent component analysis. ACWD was validated for 45 healthy and 4 arrhythmic fetuses ranging from 22 to 37 weeks; ACWD outcomes were compared with the estimates of three independent investigators. Descriptive sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Afterward, the fetal cardiac components were separated from the maternal ones on the basis of the heart rate, which is calculated by means of an adaptive detection of the R peaks. For further details on this procedure, the interested reader is addressed to Comani et al (2005b).…”
Section: Fmcg Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Afterward, the fetal cardiac components were separated from the maternal ones on the basis of the heart rate, which is calculated by means of an adaptive detection of the R peaks. For further details on this procedure, the interested reader is addressed to Comani et al (2005b).…”
Section: Fmcg Data Processingmentioning
confidence: 99%
“…At least three traces were used, and simultaneous rhythm strips of no less than 70 consecutive cardiac cycles were analyzed. The P-QRS-T waves were detected on single cycles (figure 2(b)) with an automatic procedure already assessed by the authors (Comani et al 2005b). For each heartbeat, the instants corresponding to the onset and offset of the P-QRS-T waves were used to calculate the duration of the P wave, PR interval, QRS complex, ST segment, T wave and QT interval.…”
Section: Calculation and Assessment Of The Fctimentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we have demonstrated that independent component analysis (ICA) could be efficiently applied to fMCG to reconstruct reliable fetal traces affected by negligible noise contamination (Comani et al 2004a, 2004b, 2004c, 2004d, 2005c, 2005b, Brisinda et al 2005, Mantini et al 2004. However, the effectiveness of ICA is highly dependent on the signal-to-noise ratio of input recordings, as it is particularly evident when fMCG recorded in an unshielded hospital setting is processed: the high level of ambient noise, in fact, may impede the extraction of dependable fetal magnetocardiograms for fetuses of less than 30 weeks (Brisinda et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However this method may show multiple errors in case of fluctuation around the R-peak especially if this peak was not precisely situated at the maximum [9][10][11][12]. To resolve these problems, we preformed firstly a local correction of the given position of R-peak by comparing the sign of derivative before and after R-peak in order to ensure that is situated at the maximum.…”
Section: B Complexes Extractionmentioning
confidence: 99%